2022
DOI: 10.1364/optica.458330
|View full text |Cite
|
Sign up to set email alerts
|

Space–ground QKD network based on a compact payload and medium-inclination orbit

Abstract: Significant progress has been made in satellite-based quantum key distribution (QKD), and urgent follow-up work is to explore the optimal solution for building practical quantum constellations. Here, we demonstrate successful QKD based on the compact terminal on the Tiangong-2 Space Lab and construct a space–ground quantum network among four ground stations. The medium-inclination orbit of Tiangong-2 Space Lab can obtain multiple available passes for the same ground station in one night, increasing the key gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…L pe (ρ) = L pe (∆x, ∆y) = ˆA I l (x + ∆x, y + ∆y, z) dxdy (8) where (∆x) 2 + (∆y) 2 = ρ 2 . Replace the telescope area A with a square aperture of area π (D R /2) 2 .…”
Section: State-dependent Misalignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…L pe (ρ) = L pe (∆x, ∆y) = ˆA I l (x + ∆x, y + ∆y, z) dxdy (8) where (∆x) 2 + (∆y) 2 = ρ 2 . Replace the telescope area A with a square aperture of area π (D R /2) 2 .…”
Section: State-dependent Misalignmentmentioning
confidence: 99%
“…Based on quantum mechanics, QKD could provide information-theoretic approach against an eavesdropper during key distribution tasks [1][2][3]. Currently, along with the breakthrough of fiber-based [4][5][6] and satellite-based [7,8] quantum communication, building and operating a high-efficient and flexible quantum internet has become a grand vision attracting global attention [9,10]. However, most of these achievements are based on encoding information with two-dimensional quantum systems such as polarization and phase of photons.…”
Section: Introductionmentioning
confidence: 99%
“…Tiangong-2 Space Lab is a Chinese space station orbiting in a LEO at medium inclination. It has been used as a testbed for a trusted relay for a QKD experiment, achieving a sifted key generation rate of 1.33 Mb per day under best-case conditions (Li et al, 2022). This experiment showed that by combining satellites in sun synchronous orbit (SSO) and medium inclination orbit (MIO), a higher overall key rate per day can be achieved due to the multi-pass benefit of MIOs.…”
Section: Key Generation -Synchronous Vs Stockpiledmentioning
confidence: 99%
“…More recently, there have been QKD experiments performed on actual space-ground optical downlinks from LEO, most notably using the satellite Micius under the auspices of the Chinese QUESS program (Liao et al, 2017) and Tiangong-2 Space Lab (Li et al, 2022). These experiments show that whilst their key generation rate is still too miniscule to be useful in an IoT backhaul application, the concept of satellite-based QKD is at least feasible and now needs only to be scaled up.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most accessible technologies in this regard are the quantum key distribution (QKD) protocols to ensure secure communication [15][16][17]. The QKD networks have been deployed in large metropolitan settings [18][19][20][21][22], and have also been operationally demonstrated in networks connecting ground stations using satellites as trusted nodes [23][24][25][26][27], highlighting the utility of this approach.…”
Section: Introductionmentioning
confidence: 99%